2016
DOI: 10.4049/jimmunol.1501272
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Synthesis of Cyclic-di-GMP Using a Recombinant Adenovirus Preferentially Improves Adaptive Immune Responses against Extracellular Antigens

Abstract: There is a compelling need for more effective vaccine adjuvants to augment induction of antigen specific adaptive immune responses. Recent reports suggested the bacterial second messenger bis-(3′–5′)-cyclic-dimeric-guanosine monophosphate (c-di-GMP) acts as an innate immune system modulator. We recently incorporated a Vibrio cholerae diguanylate cyclase (DGC) into an adenovirus (Ad) vaccine, fostering production of c-di-GMP as well as pro-inflammatory responses in mice. Here, we recombined a more potent DGC, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…[ 97 , 114 , 150 , 151 ]. Others have attempted to synthesize c-di-GMP in vivo by transducing a diguanylate cyclase gene into the nonreplicating adenovirus serotype 5 (Ad5) vector, which produced enhanced amounts of c-di-GMP when expressed in mammalian cells in vivo [ 152 , 153 ]. Furthermore, cGAMP has been incorporated into viral particles such as lentivirus and herpesvirus virions [ 154 ].…”
Section: Novel Delivery Strategies To Enhance the Immunostimulatory And Adjuvant Function Of Cdnsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 97 , 114 , 150 , 151 ]. Others have attempted to synthesize c-di-GMP in vivo by transducing a diguanylate cyclase gene into the nonreplicating adenovirus serotype 5 (Ad5) vector, which produced enhanced amounts of c-di-GMP when expressed in mammalian cells in vivo [ 152 , 153 ]. Furthermore, cGAMP has been incorporated into viral particles such as lentivirus and herpesvirus virions [ 154 ].…”
Section: Novel Delivery Strategies To Enhance the Immunostimulatory And Adjuvant Function Of Cdnsmentioning
confidence: 99%
“…Furthermore, cGAMP has been incorporated into viral particles such as lentivirus and herpesvirus virions [ 154 ]. The proof of concept of these approaches has been demonstrated in animal models with extracellular protein Ova, HIV-1 Gag peptides, or the C. difficile toxin B [ 152 , 153 ]. Quintana and colleagues have explored the feasibility to engineer a live Lactococcus lactis vector containing a single plasmid with both cdaA and tscf genes under different promoters, respectively, to simultaneously synthesize the adjuvant c-di-AMP as well as a heterologous vaccine antigen of interests in order to develop a simple and economical system for vaccine development [ 155 ].…”
Section: Novel Delivery Strategies To Enhance the Immunostimulatory And Adjuvant Function Of Cdnsmentioning
confidence: 99%
“…As the preponderance of efforts to activate STING has relied on injection of natural CDNs or other small molecule STING agonists, either free or incorporated into delivery systems like nanoparticles, there is little research exploring harnessing the power of CON synthases to activate STING ( figure 4 c ). We have shown that the gene encoding two DGCs from the bacterial pathogen V. cholerae delivered into eukaryotic cells using an adenovirus type 5 delivery vector can synthesize high concentrations of intracellular c-di-GMP that robustly activates STING both in vitro in cell culture and in vivo in mouse models [ 118 , 119 ]. Such activation enhances both innate and adaptive immune responses.…”
Section: Advantages Of Using Naturally Occurring Cdns To Activate Stingmentioning
confidence: 99%
“…169 In a more recent study, they combined VCA0848 (more potent dgc) with nonreplicating adenovirus serotype 5 (AdVCA0848) for an improved stimulation of innate immunity in mice. 170 On the other hand, the Gursel group used the arginine peptide (positively charged) to complex with c-di-GMP (negatively charged) for delivery into mouse cells with enhanced immunostimulation of c-di-GMP being observed. 168 In addition, Hayakawa loaded c-di-GMP on liposomes (YSK05 lipid), facilitating the delivery of c-di-GMP directly into the cytosol.…”
Section: Cyclic Dinucleotides As Anticancer Agents or Cancer Immune Amentioning
confidence: 99%